2008
DOI: 10.1242/jcs.013755
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced recruitment of epiplakin to keratin networks increases their resistance to hyperphosphorylation-induced disruption

Abstract: Epiplakin is a large (>725 kDa) cytoskeletal protein exclusively expressed in epithelial tissues. It has a unique structure, consisting entirely of plakin repeat domains (PRDs), one of the hallmarks of spectraplakin protein family members. Previous studies, including the phenotypic analyses of knockout mice, failed to reveal the biological function of epiplakin. Using in vitro binding assays, we show here that all but one of the 16 PRDs of mouse epiplakin bind to keratins of basal keratinocytes. Nevertheless, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 38 publications
(66 reference statements)
1
19
0
Order By: Relevance
“…The binding of EPPK to K5/K14 has been reported previously [3,5]. The association of EPPK with other keratins, as suggested by our observations, remains to be confirmed by analyses in vitro.…”
Section: Discussionsupporting
confidence: 84%
“…The binding of EPPK to K5/K14 has been reported previously [3,5]. The association of EPPK with other keratins, as suggested by our observations, remains to be confirmed by analyses in vitro.…”
Section: Discussionsupporting
confidence: 84%
“…This finding and epiplakin’s unique structure comprising 16 similar PRDs, most of which bind to keratins [12] suggest that keratins are epiplakin’s most important and probably sole binding partners in acinar cells. ii) During acute pancreatitis epiplakin and keratins are upregulated in a concerted manner in both mice and humans, indicating a close functional relationship.…”
Section: Discussionmentioning
confidence: 87%
“…We and others generated epiplakin knock-out (EPPK −/− ) mice, which, surprisingly, showed no obvious spontaneous or stress-induced in vivo phenotype [10], but accelerated migration of keratinocytes ex vivo [11]. Subsequent analyses revealed that epiplakin protects from hyperphosphorylation-induced keratin disruption in keratinocytes, thereby indicating a function in stress response [12]. Epiplakin interacts with keratin 8 and 18 (K8 and K18), the main keratins expressed in simple epithelia [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is unusual in that it consists solely of 13 plakin repeat domains ( Figure 1). Its function is unknown although one report has suggested that it may play a role in protecting keratin intermediate filaments from damage when cells are exposed to UV radiation and other forms of stress (Spazierer et al, 2008). To date no diseases have been linked to mutations in either the MACF1 or epiplakin genes.…”
Section: Macf1 and Epiplakinmentioning
confidence: 99%